1996
DOI: 10.1002/pssa.2211530127
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of F-aggregate centers in thermal neutron irradiated LiF TLD-100 single crystals

Abstract: On excitation with 445 nm light, thermal neutron and γ‐ray irradiated thermoluminescent dosimetry (TLD) grade LiF TLD‐100 single crystals exhibit green photoluminescence (PL) emission with a peak around 521 nm characteristic of F3+ centers and a red PL emission peaking around 656 nm characteristic of F2 centers. At low dose levels, the 515 to 653 nm PL intensity ratio for thermal neutrons is nearly three times higher when compared to that for γ‐rays. The results are discussed on the basis of the trap structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…The sensitivity of LiF to ionizing radiation is used in dosimetry [5]. In [6], it is shown that color centers on the surface of LiF can considerably increase the adhesion strength of silver and gold films on this surface.…”
mentioning
confidence: 99%
“…The sensitivity of LiF to ionizing radiation is used in dosimetry [5]. In [6], it is shown that color centers on the surface of LiF can considerably increase the adhesion strength of silver and gold films on this surface.…”
mentioning
confidence: 99%
“…(11), (13), (14) and on further consideration, we assumed the absence of electrons in traps. However, this assumption does not affect the conclusion concerning the relative efficiency of reactions (2) and (4). Below we will find that the presence of electrons in traps is not supported by the experimental results.…”
mentioning
confidence: 89%
“…Note that the concentration of F 1 centers and interstitial fluorine atoms are close in value, and much higher than the concentration of interstitial fluoride ions. Therefore the probabilities of processes (8) and (4) are much higher than the probability of process (2). The values found for the activation energies and lifetimes of vacancies and F 2 + centers will be used in analysis of the processes forming F 2 and F 3 + color centers.…”
mentioning
confidence: 98%
“…For instance, colour centres (CC's) [3] in lithium fluoride (LiF) are well known for their application in tuneable solid-state lasers [4], dosimeters [5], and miniaturized light-emitting devices [6]. Certain types of CC's in LiF are optically active, stable at room temperature, and possess broad absorption and emission bands in the visible [7].…”
Section: Introductionmentioning
confidence: 99%